Radiolabeled Chalcone Derivatives as Potential Radiotracers for β-Amyloid Plaques Imaging - Pier Cesare Capponi; Matteo Mari; Erika Ferrari; Mattia Asti (Molecules, 2023)
Natural products often provide a pool of pharmacologically relevant precursors for the development of various drug-related molecules. In this review, the research performed on some radiolabeled chalcone derivatives characterized by the presence of the α-β unsaturated carbonyl functional group as potential radiotracers for the imaging of β-amyloids plaques will be summarized. Chalcones’ structural modifications and chemical approaches which allow their radiolabeling with the most common SPECT (Single Photon Emission Computed Tomography) and PET (Positron Emission Tomography) radionuclides will be described, as well as the state of the art regarding their in vitro binding affinity and in vivo biodistribution and pharmacokinetics in preclinical studies. Moreover, an explanation of the rationale behind their potential utilization as probes for Alzheimer’s disease in nuclear medicine applications will be provided.